2017
DOI: 10.1128/aac.01204-16
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance Gene mcr-1 and Its Variant in Escherichia coli Isolates from Chickens in China

Abstract: The mcr-1 gene was detected in 5.11% (58/1136) of Escherichia coli isolates of chicken origin from 13 provinces in China. A novel mcr-1 variant, named mcr-1.3, encoding an Ile-to-Val functional variant of MCR-1 was identified in a sequence type 155 (ST155) strain. An mcr-1.3-containing IncI2 plasmid, pHeN867 (60,757 bp), was identified. The transfer of pHeN867 led to a 32-fold increase in the MIC of colistin in the recipient, exhibiting an effect on colistin resistance that was similar to that of mcr-1. KEYWOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 20 publications
6
58
3
2
Order By: Relevance
“…CTX-M-producing enterobacteria are widespread among human populations, but an increasing number of reports have described their presence in food animals and their environment (Li et al, 2007;Ewers et al, 2012;Lazarus et al, 2015). In the present study, 88.2% of the mcr-1 positive isolates carried bla CTX−M , which was similar to a previous study in which more than half of the chicken-origin mcr-1 positive strains presented the coexistence of the mcr-1 and bla CTX−M genes (Yang et al, 2017), but higher than the 43.1% mcr-1 positive isolates carrying bla CTX−M genes. The increasing prevalence and dissemination of co-carriage of ESBL genes in mcr-1 positive E. coli isolates found in our study suggested that it may add challenge to the global problem of difficult to treat and untreatable infections.…”
Section: Discussionsupporting
confidence: 89%
“…CTX-M-producing enterobacteria are widespread among human populations, but an increasing number of reports have described their presence in food animals and their environment (Li et al, 2007;Ewers et al, 2012;Lazarus et al, 2015). In the present study, 88.2% of the mcr-1 positive isolates carried bla CTX−M , which was similar to a previous study in which more than half of the chicken-origin mcr-1 positive strains presented the coexistence of the mcr-1 and bla CTX−M genes (Yang et al, 2017), but higher than the 43.1% mcr-1 positive isolates carrying bla CTX−M genes. The increasing prevalence and dissemination of co-carriage of ESBL genes in mcr-1 positive E. coli isolates found in our study suggested that it may add challenge to the global problem of difficult to treat and untreatable infections.…”
Section: Discussionsupporting
confidence: 89%
“…The mcr‐1 was present in 172 (12.6%) of E. coli isolates in China, from 2015 to 2017. The prevalence of mcr‐1 in avian‐origin E. coli was higher than that reported by Yang et al, (). Over time, the mcr‐1 gene was the more frequently observed in avian‐origin E. coli .…”
Section: Discussioncontrasting
confidence: 64%
“…The mcr‐1 gene was detected in 5.11% (58/1136) of chicken‐origin E. coli isolates from 13 provinces in China, from 2010 to 2015 (Yang et al, ). Half of the chicken‐origin MCRPEC strains presented the coexistence of mcr‐1 and bla CTX‐M genes (Yang et al, ). In this study, our result confirmed the aforementioned findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations